B and Ga Co-Doped Si1−xGex for p-Type Source/Drain Contacts. (1st February 2022) - Rengo, Gianluca; Porret, Clement; Hikavyy, Andriy; Rosseel, Erik; Ayyad, Mustafa; Morris, Richard J. H.; Khazaka, Rami; Loo, Roger; Vantomme, André
Abstract : Contact resistivity reduction at the source/drain contacts is one of the main requirements for the fabrication of future MOS devices. Current research focuses on methods to increase the active doping concentration near the contact region in silicon-germanium S/D epilayers. A possible approach consists in adding co-dopants during the epitaxy process. In the case of p-MOS, gallium can be used in addition to boron. In this work, the properties of in situ Ga and B co-doped Si0.55 Ge0.45 layers are discussed. The surface morphologies, layer compositions, structural and electrical material properties are described and compared with those of a B-doped Si0.55 Ge0.45 reference layer. Ga segregation occurring at the growth surface is evidenced. Post-epi surface cleans are required to obtain the correct Ga profiles in the Si1−x Gex layers from secondary ion mass spectrometry, otherwise altered by surface Ga knock-on. The layer morphologies, crystalline quality and electrical properties show a progressive degradation with increasing Ga dose. Finally, specific titanium-Si1−x Gex :B(:Ga) contact resistivity values have been extracted using the multi-ring circular transmission line method. The contact resistivity is lower for the Ga co-doped samples, the best contact properties ( < 3 × 10 −9 Ω.cm 2 ) being obtained for the sample grown with the lowest Ga-precursor flow.